The history of the Black Watch (Royal Highland Regiment) of Canada - Jarymowycz, Roman Johann, 1945-2017 (McGill-Queen's University Press, 2023)
"The Black Watch (RHR) is Canada's senior Highland regiment. Its history reaches back to the origins of Canada itself. Its enviable battle honours proclaim profound loyalty to country, King and Queen. Its reputation in battle (as witness the six Victoria Crosses awarded in the Great War) and dozens of military engagements through three centuries, have given the Regiment legendary status. The Regiment commissioned Lieutenant Colonel Roman Jarymowycz to write this history and has enthusiastically encouraged this mammoth undertaking. The author traces the history of the Regiment from its 18th century roots, when soldiers, settlers, and militia volunteers rallied to the cause of their adopted country. As well. the story reviews the early defence of Canada from American invasion and the formation of Scottish companies and battalions before and after Confederation."--